72.6k views
2 votes
4. I need help with question in the attached picture!

4. I need help with question in the attached picture!-example-1
User Surega
by
6.1k points

2 Answers

2 votes

Answer:

Option D is correct.

Explanation:


f(x)= (2x+1)/(x-4) \,\,find \,\,value\,\,of\,\, f^(-1)(3)

We know that f(a) =b ⇔ f^-1 (b) =a

Using this,

We are given
f^(-1)(3)=x => f(x)=3

and
f(x)= (2x+2)/(x-4)

putting value of f(x)


3= (2x+1)/(x-4)\\3(x-4) = 2x+1\\3x-12 = 2x+1\\Adding\,\,like\,\,terms\,\,\\3x-2x = 12+1\\x=13\\So, f^(-1)(3) = 13

Option D is correct.

User Marc SJ
by
5.2k points
3 votes

ANSWER

D. 13

EXPLANATION

We have


f(x) = (2x + 1)/(x - 4)

To find


{f}^( - 1) (3)

means we want to find an x-value whose image is 3.


(2x + 1)/(x - 4) = 3

We cross multiply,


2x + 1 = 3(x - 4)

Expand:


2x + 1 = 3x - 12

Combine like terms,


3x - 2x = 12 + 1


x = 13


\therefore{f}^( - 1) (3)= 13

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.